(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The research regarded the specific composition of spider fauna collected in vineyards of two areas of Northern Italy (territory of Ghemme in Novara province and vineyards in Brescia province) using pitfall-traps in the course of two vegetative seasons (1993 and 1994). Specimens of 73 species were collected, some present in both areas, some in one only. That is nearly the 5% of the species recorded from Italy in the Checklist of the Italian fauna species, witnessing a good presence of spiders, important natural predators.